Educaplay as an Interactive Digital Media for Students' HOTS Thinking on Living Things Material - Nur'aeni, Amellia Putri; Harianingsih, Harianingsih; Avrilianda, Decky; Ellianawati, Ellianawati (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to determine the effectiveness of Educaplay interactive digital media in improving the Higher Order Thinking Skills of grade II elementary school students on the subject of living things. The study used a quantitative approach with a quasi-experimental design of the One-Group Pretest-Posttest Design type. The subjects of the study were 20 grade II students of SDN Karawang Kulon II. The instruments used were multiple-choice HOTS tests and descriptions based on the revised Bloom's taxonomy, with indicators of analyzing, evaluating, and creating. The results showed that there was a significant increase in the posttest score compared to the pretest, with an average increase of 41.1 points and a significance value of 0.001 (p <0.05). The N-Gain value was in the medium to high category (average 0.6867). In addition, the analysis of the quality of the questions showed that most of the questions were difficult and had good discriminating power. These findings indicate that Educaplay is effective in developing students' HOTS skills through interactive, contextual, and fun learning. The implications of this Research encourage teachers to utilize digital media as a learning tool that is not only interesting but also able to stimulate high-level cognitive activities from the elementary education level.